Efficacy and safety of eltrombopag in treatment-refractory primary immune thrombocytopenia: a retrospective study - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2016)
Eltrombopag was used in patients with chronic primary immune thrombocytopenia (ITP) who did not tolerate or were refractory to two or more previous treatments. The primary aims of the study were to determine the efficacy and safety of long-term eltrombopag treatment. Data were extracted from medical chart records retrospectively. Platelet count of at least 50000/l at any time point during the treatment was defined as the response'. Median duration of eltrombopag treatment was 29 weeks (11-74). The number of patients who had a platelet count of at least 50000/l at any time point was 26 (83.9%). The response was achieved by the second week in most of the patients. Concomitant ITP medications were withdrawn in nine out of the 11 patients. Eltrombopag was discontinued in one patient due to sustained response despite discontinuation of the treatment. Age, sex, concomitant ITP treatments, and previous ITP treatment failures had no impact on the treatment response. The treatment was discontinued due to thrombosis in only four patients. Four patients experienced a minor bleeding event. Hepatotoxicity and all other adverse events were mild and manageable. Eltrombopag is effective, safe, and well tolerated in the long-term treatment of chronic ITP patients. Blood Coagul Fibrinolysis 27: 47-52 Copyright (C) 2016 Wolters Kluwer Health, Inc. All rights reserved.
Keywords: eltrombopag; immune thrombocytopenic purpura; thrombopoietin receptor agonist; LONG-TERM TREATMENT; PLATELET COUNTS; CHRONIC ITP; PURPURA; MANAGEMENT; ADULTS; PATHOPHYSIOLOGY; SPLENECTOMY; ROMIPLOSTIM; PERSPECTIVE